Unity Of Ummah Mahmud Yunus's Perspective In Tafsir Al-Qur'an Al-Karim - Hidayatullah Ismail; Nasrul Fatah; Jani Arni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Tafsir Al-Qur'an Al-Karim which is the great work of Mahmud Yunus who is known as one of the productive Indonesian scholars has produced written works in various Islamic disciplines. This interpretation is always interesting to study because its style is thick with the nuances of ijtima'i as a form of response to the realities of life that exist in society. Among the descriptions found in many places in this commentary is the importance of maintaining unity and integrity and avoiding disintegrity. So this paper aims to analyze Mahmud Yunus's thoughts on the unity of the people with a descriptive approach to analysis based on library data. The findings of this study found that efforts to realize unity among Muslims must continue to be carried out even though big challenges always exist. Challenges to the union came from external and internal. External, namely from parties outside Islam who do not want the realization of Muslim unity. While internal comes from within the body of Muslims caused by not adhering to the Qur'an and sunnah and the nature of ta'ashub. As a solution offered is to strengthen moral education or tarbawi akhlaqi in social life